The Oxford dictionary of rhyming slang / Edited by John Ayto - Ayto, John Editor
Rhyming slang is a subject of perennial interest to the general language-conscious public. Entries are arranged in subject areas, such as clothing, food and drink, and animals. John Ayto explores the range and development of rhyming slang during its 150 year history, from traditional Cockney Rhyming Slang to the popney rhyming slang of today.